Fotos de Béisbol: An Examination of the Spanish-language Instagram Accounts of Major League Baseball Teams. Issue 3 (27th May 2019) - Hull, Kevin; Kim, Joon Kyung; Stilwell, Matt
ABSTRACT: Although every Major League Baseball team has an official English-language Instagram account, only 2 have a Spanish-language account. The purpose of this study is to examine how those accounts attempt to reach Hispanic fans. An examination of all the posts from the 2 Spanish-language accounts from the entire 2016 season demonstrate that the accounts do actively showcase more Hispanic players and cultural events. Further analysis demonstrates that posts with a Hispanic element register more user engagement than posts that do not. Theoretical implications regarding social identity theory and practical implications for professional sports teams are discussed.